Wildlife Poaching: An Environmental Law Analysis of Transnational Organized Crime Networks - Kartina Pakpahan; Sri Sulistyawati; Willy Tanjaya; Sigar P. Berutu (Nusantara: Journal of Law Studies, 2026)
Wildlife poaching has increasingly become part of transnational organized crime networks that threaten biodiversity conservation and weaken environmental governance in many regions, including Aceh, Indonesia. This study aims to analyze wildlife poaching in Aceh from an environmental law perspective, with particular attention to the legal frameworks, enforcement mechanisms, and institutional challenges in addressing transnational wildlife crime. The research seeks to identify how existing legal instruments regulate wildlife protection and assess the extent to which these regulations can address organized criminal networks involved in illegal wildlife trade. This study employs a qualitative juridical approach using normative and empirical legal analysis. The research examines national environmental and wildlife protection laws, international legal instruments, and relevant enforcement practices related to wildlife crime. Data were collected through document analysis of legislation, policy reports, and scholarly literature, complemented by secondary data on wildlife crime cases in Aceh. The analytical framework integrates environmental law, transnational organized crime studies, and green criminology to understand the legal and institutional dynamics surrounding wildlife poaching. The findings reveal that wildlife poaching in Aceh is not merely a local environmental offense but is closely connected to broader transnational trafficking networks that exploit regulatory gaps, limited enforcement capacity, and coordination challenges among institutions. Although Indonesia has established several legal instruments to protect wildlife and combat environmental crimes, weaknesses remain in implementation, cross-border cooperation, and the integration of environmental law with criminal justice mechanisms. Strengthening institutional coordination, improving investigative capacity, and aligning domestic regulations with international frameworks are essential to addressing the complexity of wildlife crime networks. This study contributes to the growing discourse on environmental law and transnational environmental crime by providing a legal analysis of wildlife poaching within the context of organized criminal networks.